The Economics of Breakdowns, Checkups, and Cures - Taylor, Curtis R. (Journal of Political Economy, 1995)
A market in which the owner of a durable good, X, contracts with an expert for diagnostic and treatment services is studied. Good X may be in one of three states: "health," "disease," or "failure." Only experts can determine whether X is healthy or diseased and perform treatment. The owner cannot tell whether recommended treatment is really needed. This creates an information-based demand for health insurance by risk-neutral consumers. Imperfections in the market for spot insurance may give rise to free diagnostic checks, strategic procrastination, and long-term health maintenance agreements.